Implementasi Program Bantuan Asistensi Rehabilitas Sosial (ATENSI) Kepada Masyarakat Muslim Penyandang Disabilitas Di Kecamatan Binjai Kabupaten Langkat - Fadhillah, Luthfiah Fitri; Tanjung , Muaz (Jayapangus Press, 2024)
This study aims to determine how the implementation and inhibiting and supporting factors of the Social Rehabilitation Assistance Program (ATENSI) aimed at Muslim communities with disabilities in Binjai District, Langkat Regency. The provision of social rehabilitation assistance is important in creating social inclusion for disability groups, especially those who are Muslim. The method used is qualitative with a qualitative descriptive approach. The results of the research are: ATENSI activities for people with disabilities are made through implementation by providing fulfillment of basic needs, skills or entrepreneurship. The Langkat District Social Service has launched an innovative program to help Muslim communities with disabilities including the provision of social assistance in the form of food, clothing, skills training, and socialization to improve the quality of life. a separate obstacle by the Langkat District Social Service due to the limited number of recipients compared to the population of people with disabilities in Langkat District. This is closely related to budget limitations that have not been able to fully reach the entire population that needs this assistance. In dealing with this obstacle, the Social Service of Langkat Regency paid special attention and expressed the hope that with the development of the APBD budget capability of Langkat Regency, this program could be further expanded. Conclusion The implementation of Social Rehabilitation Assistance (ATENSI) activities provided to people with disabilities is right on target and on target so that it is able to improve welfare for people with disabilities.